2017
DOI: 10.1016/j.cotox.2017.01.012
|View full text |Cite
|
Sign up to set email alerts
|

The aryl hydrocarbon receptor (AhR) as a drug target for cancer chemotherapy

Abstract: The aryl hydrocarbon receptor (AhR) is overexpressed in some patients with different tumor types, and the receptor can be a negative or positive prognostic factor. There is also evidence from both in vivo and in vitro cell culture models that the AhR can exhibit tumor-specific pro-oncogenic and tumor suppressor-like functions and therefore can be treated with AhR antagonists or agonists, respectively. Successful clinical applications of AhR ligands will require the synthesis and development of selective AhR mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
61
0
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(67 citation statements)
references
References 57 publications
(54 reference statements)
2
61
0
1
Order By: Relevance
“…Recent evidence of DIM derivatives as chemopreventive agents against triple negative breast cancer hold promise from early demonstration studies of in vitro models[51]. Tumor-specific responses have also been described including aryl hydrocarbon receptor (AhR) agonistic activity [52] and sensitizing activity against gamma radiation [53]. These alternate pathways for chemopreventive activity are under active study and could be further explored using stored biosamples from the current trial.…”
Section: Discussionmentioning
confidence: 99%
“…Recent evidence of DIM derivatives as chemopreventive agents against triple negative breast cancer hold promise from early demonstration studies of in vitro models[51]. Tumor-specific responses have also been described including aryl hydrocarbon receptor (AhR) agonistic activity [52] and sensitizing activity against gamma radiation [53]. These alternate pathways for chemopreventive activity are under active study and could be further explored using stored biosamples from the current trial.…”
Section: Discussionmentioning
confidence: 99%
“…The aryl hydrocarbon receptor (AhR) is a member of the basic helix‐loop‐helix/Per‐ARNT‐SIM (bHLH/PAS) transcription factor family, and it has been previously suggested that it is a possible druggable target . It is ligand activated by a variety of synthetic and natural compounds .…”
Section: Aryl Hydrocarbon Receptormentioning
confidence: 99%
“…IDO is activated in tumor, stromal, and innate immune cells in various cancers, and its expression is correlated with a less favorable prognosis [20]. Increased TDO2 expression is associated with a higher grade, estrogen receptor-negative status, and a shorter overall survival (OS) in triple-negative breast cancer [21], whereas AhR overexpression in several cancers can be a positive or negative prognostic factor, depending on the type of cancer [22]. High AhR expression in breast cancer correlates with higher expression of several genes in inflammation, endogenous Trp metabolism, and the invasion signaling pathway [23].…”
Section: Introductionmentioning
confidence: 99%